Implementasi Indikator Moderasi Beragama Pada Kearifan Lokal Paguyuban Mejing Tabon Yogyakarta untuk Mewujudkan SDG’s United Nations - Robikhah, Aridlah Sendy; Bettaliyah, Azza Abidatin; Oktavianti, Arindah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The Mejing Tabon Community consists of people with diverse religious backgrounds. Local wisdom is needed to maintain harmony amidst religious heterogeneity, which contains moderate indicators. This local wisdom is one of the unifying factors of the Mejing Tabon Community Association to avoid social conflict. This aligns with SDG's 16, which focuses on advancing peace and justice. Therefore, this research aims to explain the application of religious moderation indicators in the local wisdom of Mejing Tabon so that it contributes to achieving the SDGs. This research uses qualitative methods with a sociological approach. As for the results of this research, there are four indicators of religious moderation, namely National Commitment, Tolerance, Non-Violence, and Acceptance of Tradition, which have been reflected in the local wisdom of the 5 Principal Calendars implemented yearly. Thus, this local wisdom also contributes to achieving National and Global Targets related to Peace and Justice.